Shoulderology - Itoi, E. (Springer Singapore, 2023)
This Monograph is a compilation of clinical experience and basic research by the author on the function and anatomy of the shoulder joint, with particular emphasis on biomechanics. The book provides deep and comprehensive knowledge about the shoulder based on the author`s over forty years of career. This book is unique in that it emphasizes the process of discovering new knowledge through searching for clinical questions or "whys" and solving them. The author shows how he tackled various problems with a great deal of medical curiosity. The chapters place much space on anatomy, function, and pathology, for correct treatment through an accurate understanding of the pathology. The first part of this book explains the basic examination methods as clearly as possible, with abundant figures taken during patient consultations. Part two through four describes some diseases of the shoulder joint, including rotator cuff tears, instability, frozen shoulder, biceps disorders, and throwing shoulder, all of which are frequently encountered in daily practice. In part five, biomechanical research related to suture anchors is presented, and correct insertion angles and intervals are described. It is crucial to understand the surgical method correctly and question the commonly used techniques for better patient care. A clear explanation of long-standing debates, such as the deadman theory, is explained based on the evidence from his research. The last part presents two cases that are rarely encountered but are interesting from the perspective of functional reconstruction of the shoulder.